We need to drive change for the future and support junior trainees whilst maintaining the highest training standards. Issue 10 (December 2020) - Boyapati, R.; Glen, P.; Garg, M.
Abstract: The oral and maxillofacial surgery (OMFS) community in the UK has always felt distinguished to be the only surgical specialty requiring dual qualification. There is no doubt that OMFS recruitment in the UK is in crisis, and we believe that the time has arrived to review the long training pathway. Policy-makers should think of alternative options to make the training programme more sustainable whilst maintaining the highest standards. The problem is serious, and the onus is on all consultants and higher surgical trainees. An urgent multi-pronged, structured approach is required to improve recruitment. It is important to find ways to reduce the training time whilst supporting trainees through their second degree. Consultants and higher surgical trainees need to come forward to participate in the BAOMS working group to create regional career mentors and part-time career development posts for potential trainees. We need to drive change for the future and support junior trainees whilst maintaining the highest training standards.